Monetary Models and Inflation Targeting in Emerging Market Economies. - FitzGerald, V (Department of Economics (University of Oxford), 2004)
This paper extends and modifies the Keynesian critique of inflation targeting with reference to stabilisation policy in emerging market economies. The IMF 'basic monetary programming framework' for developing countries uses government borrowing and the exchange rate as policy instruments in order to achieve specific inflation and balance of payments targets. This paper first adapts this standard model in order to include short-term capital flows and the floating exchange rate arising from financial liberalisation. In this way, the macroeconomic consequences of the current Fund focus on inflation targeting and the use of a single monetary policy instrument (the interest rate, combined with rigid fiscal and reserve 'rules') in emerging market economies can be demonstrated. Second, the paper encompasses the structuralist critique of the negative effect of inflation targeting on capacity utilisation and trade competitiveness, leading to an argument for counter-cyclical monetary policy in response to external shocks. An alternative model is constructed within a comparable macroeconomic framework to that of the IMF in order to permit the shortcomings of inflation targeting to be rigorously demonstrated. A macroeconomic stabilisation policy based on real exchange rate targeting, bank credit regulation and an active fiscal stance is shown to be more effective in supporting growth and investment.